Implementasi pembelajaran mendalam (Deep learning) pada mata pelajaran Fiqih di Madrasah Ibtidaiyah - Esi Ifadah; Umi Rosidatul Koiroh; Hawin Musyafa; Irmawati; A. Fauzi; Iis Arifudin (Jurnal Pendidikan Agama Islam, 2026)
Deep learning is an educational approach that centers on thorough conceptual understanding rather than surface-level memorization. It calls for active student participation, critical reasoning, and the ability to bridge classroom knowledge with real-world contexts. This study examines the implementation of deep learning in Fiqh instruction at Madrasah Ibtidaiyah. Using a qualitative descriptive method, data were gathered through observation, interviews, and documentation. Findings show that deep learning improved students' grasp of worship-related content, strengthened critical thinking skills, and nurtured students' religious character. Teachers employed strategies such as group discussions, direct religious practice, reflective activities, and problem-solving grounded in students' daily experiences. Challenges included a shortage of instructional media, varied student abilities, and limited class time. Despite these constraints, deep learning proved effective in elevating the quality of Fiqh education at the Madrasah Ibtidaiyah level.